Family Impacts on Self-Esteem in Chinese College Freshmen - Shi, Jingyu; Wang, Lu; Yao, Yuhong; Su, Na; Zhao, Xudong; Chen, Fazhan (Frontiers in Psychiatry, 2017)
This study examined the impact of family function and family-related factors, such as being an only child, grandparenting, income, and family relationship on the self-esteem in college students who are in the transitional period from late adolescence to emerging adulthood. The participants were 2001 Chinese college freshmen with the age from 16 to 20 years. Data were collected by using the family assessment device (FAD), the Rosenberg Self-esteem Scale, and self-report of family information. Comparison analysis indicated that the students from one child families, harmonious families, from families with higher income, or raised by their parents without the experience of grandparenting are more likely to show high self-esteem than their counterparts. Moreover, a multiple regression showed that dimensions of FAD such as role, communication, behavioral control, and problem solving predicted level of self-esteem of the college students, ranging from 13.2 to 17.9% variance. The results of this study showed that the self-esteem of the college freshmen is highly correlated with their family’s performance. Therefore, the program focusing on improving family functioning is needed, in order to enhance the self-esteem of the young people and hence contribute to promoting the mental health of them.